#TITLE_ALTERNATIVE# - RAHAYU (NIM : 20514003), AJENG
One of the alkaloid derivatives that have been widely explored by scientist is indole. From indoleÃ‚Â’s derivatives has been found another compound isolation such as; gramine (3-Dimethylaminomethyindole) which is from Cephaelis stipulacea and harmane (1-methyl-9H-pyrido[3,4-b]indole) which came out from leaf and bark of Ophiorrhiza communis. In the temperature range of 1050-1650 K, indoles may undergo pyrolysis to produce benzyl cyanide, o-tolunitrile, and m-tolunitrile. The compounds have benefits as an important precursor for drugs. Pyrolysis study was done both experimentally and computationally. This research also analyzes the mecanism reaction of indole pyrolysis with the computational study. The information of computational results are used to study the initial steps of pyrolysis reaction mechanism from gramine and harmane. In the pyrolysis reaction will be tested by using a DFT method and B3LYP calculation with the 6-31G(d) basis set. To determine the accuracy of the results of the indole pyrolysis becomes o-tolunitrile and m-tolunitrile in this study, then are compared with the computational study that has been done. The relative difference percentage to the results of this research have the greatest value on TS6 is equal to 35.795%. While the percentage of the smallest relative differences found in the E10 is equal to 7.456%. From these data it can be calculated the average percentage of difference relative to the results of this research that is equal to 18.161%. Pyrolysis of indole produced benzyl cyanide going through two steps, hydrogen migration and the bond cleavage of C-N. Thermodynamic studies show that the pyrolysis reaction of indole, gramine, and harmane on hydrogen migration step has a activation energy 44.279 kcal/mol; 44.183 kcal/mol and 58.010 kcal/mol respectively. In the bond cleavage of C-N step, the activation energy, respectively for 39.935 kcal/mol; 40.314 kcal/mol and 31.454 kcal/mol. The reaction rate constant calculations carried out in the temperature of 298.15 K and 1100 K. In the indole pyrolysis, the hydrogen migration in the first step has a reaction rate constant value 5.491x10-22 s-1 in the temperature of 298.15 K and 1.264x104 s-1 in the temperature of 1100 K. The bond cleavage of C-N in second step has a reaction rate constant value 3.161x10-19 s-1 in the temperature of 298.15 K and 3.926x105 s-1 in the temperature of 1100 K. In the gramine pyrolysis, the hydrogen migration in the first step has a reaction rate constant value 6.870x10-22 s-1 in the temperature of 298.15 K and 1.227x105 s-1 in the temperature of 1100 K. iv The bond cleavage of C-N in second step has a reaction rate constant value 9.013x10-20 s-1 in the temperature of 298.15 K and 3.396x105 s-1 in the temperature of 1100 K. In the harmane pyrolysis, the hydrogen migration in the first step has a reaction rate constant value 5.738x10-33 s-1 in the temperature of 298.15 K and 9.455 s-1 in the temperature of 1100 K. The bond cleavage of C-N in second step has a reaction rate constant value 1.040x10-11 s-1 in the temperature of 298.15 K and 2.072x107 s-1 in the temperature of 1100 K. At each pyrolysis reaction, hydrogen migration step has a reaction rate constant value which is smaller than bond cleavage of C-N step. The reaction rate constant for first step of harmane has the smallest value. This statement is similar with the value of the greatest activation energy. This is due to an aromatic group in harmane has led to the most stable structure. While the reaction rate constant in second step for harman has the greatest value. This is in accordance with the smallest value of activation energy. The resonantion effects cause this to happen.